Comparative proteome analysis identified CD44 as a possible serum marker for docetaxel resistance in castration‐resistant prostate cancer. Issue 4 (30th December 2021) - Keresztes, Dávid; Csizmarik, Anita; Nagy, Nikolett; Módos, Orsolya; Fazekas, Tamás; Bracht, Thilo; Sitek, Barbara; Witzke, Kathrin; Puhr, Martin; Sevcenco, Sabina; Kramer, Gero; Shariat, Shahrokh; et al.
Abstract: Baseline or acquired resistance to docetaxel (DOC) represents a significant risk for patients with metastatic prostate cancer (PC). In the last years, novel therapy regimens have been approved providing reasonable alternatives for DOC‐resistant patients making prediction of DOC resistance of great clinical importance. We aimed to identify serum biomarkers, which are able to select patients who will not benefit from DOC treatment. DOC‐resistant PC3‐DR and DU145‐DR sublines and their sensitive parental cell lines (DU145, PC3) were comparatively analyzed using liquid chromatography‐coupled tandem mass spectrometry (LC‐MS/MS). Results were filtered using bioinformatics approaches to identify promising serum biomarkers. Serum levels of five proteins were determined in serum samples of 66 DOC‐treated metastatic castration‐resistant PC patients (mCRPC) using ELISA. Results were correlated with clinicopathological and survival data. CD44 was subjected to further functional cell culture analyses. We found at least 177 two‐fold significantly overexpressed proteins in DOC‐resistant cell lines. Our bioinformatics method suggested 11/177 proteins to be secreted into the serum. We determined serum levels of five (CD44, MET, GSN, IL13RA2 and LNPEP) proteins in serum samples of DOC‐treated patients and found high CD44 serum levels to be independently associated with poor overall survival ( p  = 0.001). In accordance, silencing of CD44 in DU145‐DR cells resulted in re‐sensitization to DOC. In conclusion, high serum CD44 levels may help identify DOC‐resistant patients and may thereby help optimize clinical decision‐making regarding type and timing of therapy for mCRPC patients. In addition, our in vitro results imply the possible functional involvement of CD44 in DOC resistance.